The effects of mining tailings and flood pulse on zooplankton in an Amazonian floodplain environment (Batata Lake, Pará, Brazil) - Sodré, Elder de Oliveira; Lopes, Paloma Marinho; Figueiredo-Barros, Marcos Paulo; Roland, Fábio; Esteves, Francisco de Assis; Bozelli, Reinaldo Luiz (Boletim do Museu Paraense Emílio Goeldi - Ciências Naturais, 2015)
The flood pulse, as well as anthropogenic impacts, may shape the patterns of zooplankton communities. We evaluated the influence of bauxite tailings and water levels on zooplankton at sampling times precisely defined according to the water level. Our study area was Batata Lake, an Amazonian floodplain lake impacted by bauxite tailings. Zooplankton was sampled for seven years, four times a year, at two stations, one natural and the other impacted by bauxite tailings. Zooplankton was identified to the lowest possible taxonomic level. Differences in richness and densities between periods and stations were evaluated with a two-way ANOVA. An indicator species analysis was performed to assign species to sampling stations. Community richness was lower at low water and higher at high water, whereas densities showed the opposite result. Only one species was identified as an indicator, highlighting that the zooplankton composition in natural and impacted areas was similar. Densities were also similar at these stations, except for cladocerans, which showed higher densities at the impacted station. The use of samples taken at precisely defined flood pulse periods yielded expected but refined results, as the samples were based on a precise relationship with water levels that previous studies did not include.